Impact of inconclusive endoscopic ultrasound‐guided fine‐needle aspiration results in the management and outcome of patients with solid pancreatic masses. Issue 1 (30th October 2014) - Sun, Bo; Yang, Xiujiang; Ping, Bo; He, Yiping; Zhang, Zhaozhen
<x xml:space="preserve">Abstract</x> Background and Aim Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) can be inconclusive in diagnosing solid pancreatic masses. The aim of the present study was to evaluate the impact of an inconclusive EUS‐FNA in the management of patients with solid pancreatic masses. Methods This is a retrospective analysis of a prospective database of patients with solid pancreatic masses referred for EUS‐FNA between December 2011 and December 2013. Consecutive patients with inconclusive initial EUS‐FNA were included. Demographic, clinical, procedural and outcome data were analyzed. Results Over the study period, 387 patients underwent EUS‐FNA of solid pancreatic masses, of which 38 patients had inconclusive cytology. Of the 38 patients, 18 were categorized as atypical, two were categorized as indeterminate or suspicious for malignancy, and 18 were categorized as benign process. Subsequently, 24 (63.2%) patients achieved cytopathological diagnosis by repeat EUS‐FNA (8), transcutaneous FNA (4) and surgery (12). Repeat EUS‐FNA were done a median of 13 days after the index examination and resulted in conclusive diagnosis in 72.7% of cases. Five patients undergoing surgery were confirmed to have benign lesions. In 14 (36.8%) patients not receiving a positive cytopathological diagnosis, 11 were eventually confirmed to be malignant based on clinical outcome and imaging evidence. Conclusions Inconclusive EUS‐FNA could lead to unnecessary surgical procedures in patients with resectable solid pancreatic masses if no cytopathological diagnosis is obtained through either repeat or alternative diagnostic modalities. Repeat EUS‐FNA provided a conclusive diagnosis in a majority of cases, and therefore should be strongly considered ahead of other modalities.